Preparation and structural analysis of fucomannogalactan and β-1,6-glucan from Grifola frondosa mycelium - Geng, Jie; Wang, Guining; Guo, Jiao; Han, Xiao; Qu, Yunhe; Zhou, Yifa; Tai, Guihua; Sun, Lin; Cheng, Hairong (Frontiers in Chemistry, 2023)
Polysaccharides, key components in Grifola frondosa, can be divided into those from fruiting bodies, mycelium, and fermentation broth based to their source. The structure of Grifola frondosa fruiting body-derived polysaccharides has been fully characterized. However, the structure of Grifola frondosa mycelium polysaccharides is mostly unknown. In this study, we obtained the mycelium from Grifola frondosa by liquid fermentation, and extracted them with water and alkaline solution. We then isolated and purified them to homogeneity, and systematically characterized them by methylation and by FT infrared (FT-IR) and nuclear magnetic resonance (NMR) spectroscopy. Structural analysis showed that two neutral fractions (WGFP-N-a and AGFP-N-a 1 ) have a common backbone composed of α-1,6-D-Me-Galp and α-1,6-D-Galp that were substituted at O-2 by 1,2-Manp, α-1,3-L-Fucp and α-T-D-Manp, and thus are fucomannogalactans. WGFP-A-a, AGFP-A-b and AGFP-A-c are β-1,6glucans with different molecular weights, and are branched with β-1,3-D-Glcp and T-D-Glcp at the O-3 of Glc. Our results provide important structural information on Grifola frondosa mycelium polysaccharides, and provide the basis for their further development and application.